'Leveling the playing field' when ranking accounting-education authors. (March 2019) - Bernardi, Richard A.; Collins, Kimberly Z.
Highlights: Rankings by junior, mid-level, and senior faculty. Standardized the publication counts by time and a computed measure of journal quality. Distribution of accounting-education publications for each experience groups. Benchmarking data. Significant differences in the publishing patterns between the authors from Canada and the United States and the authors from Australia, New Zealand, the Republic of Ireland, the United Kingdom. Abstract: This research employs two methods to 'level the playing field' when ranking accounting-education authors from Australia, Canada, New Zealand, the Republic of Ireland, the United Kingdom, and the United States using their publication counts in 13 accounting-education journals. The first method groups the authors so that junior, mid-level, and senior faculties are only ranked within their experience group. The second method standardizes the publication counts by the number of years since each author's PHD/DBA graduation or their first accounting-education publication whichever occurred earlier. We also adjust each author's publications using a computed measure of journal quality. In addition to our rankings using the standardized publication data by faculty group, we provide data indicating the distribution of accounting-education publications in the 13 journals for each faculty and country group. Colleagues can use the data in this research as a benchmark in the merit, promotion and/or tenure processes; external reviewers can also use the data. Finally, we note significant differences in the publishing patterns between the authors from Canada and the United States and the authors from Australia, New Zealand, the Republic of Ireland, the United Kingdom.